2019
DOI: 10.1177/0959683619854524
|View full text |Cite
|
Sign up to set email alerts
|

Integrating fire-scar, charcoal and fungal spore data to study fire events in the boreal forest of northern Europe

Abstract: Fire is a major disturbance agent in the boreal forest, influencing many current and future ecosystem conditions and services. Surprisingly few studies have attempted to improve the accuracy of fire-event reconstructions even though the estimates of the occurrence of past fires may be biased, influencing the reliability of the models employing those data (e.g. C stock, cycle). This study aimed to demonstrate how three types of fire proxies – fire scars from tree rings, sedimentary charcoal and, for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 76 publications
3
29
1
1
Order By: Relevance
“…While Simoneit et al (1999) and references therein suggest that MAs form at burn temperatures > 300 • C, several studies that have analysed the influence of various combustion conditions in natural samples indicated that MAs are thermal dehydration products at burning temperatures < 350 • C, mainly under smouldering as opposed to flaming conditions (Pastorova et al, 1993;Gao et al, 2003;Engling et al, 2006;Kuo et al, 2008Kuo et al, , 2011. A recent review of Suciu et al (2019) attributes the dominant low-temperature production to depolymerization, fragmentation and inter-and intramolecular transglycosylation during pyrolysis, while a minor fraction of MAs can attach to charcoal during higher temperatures, when smoldering overlaps with or follows flaming conditions. In Holocene lake sediments, MAs provide complementary fire proxies to sedimentary charcoal (Elias et al, 2001;Schüpbach et al, 2015;Battistel et al, 2017;Schreuder et al, 2019;Dietze et al, 2019).…”
Section: Background Considerationmentioning
confidence: 99%
“…While Simoneit et al (1999) and references therein suggest that MAs form at burn temperatures > 300 • C, several studies that have analysed the influence of various combustion conditions in natural samples indicated that MAs are thermal dehydration products at burning temperatures < 350 • C, mainly under smouldering as opposed to flaming conditions (Pastorova et al, 1993;Gao et al, 2003;Engling et al, 2006;Kuo et al, 2008Kuo et al, , 2011. A recent review of Suciu et al (2019) attributes the dominant low-temperature production to depolymerization, fragmentation and inter-and intramolecular transglycosylation during pyrolysis, while a minor fraction of MAs can attach to charcoal during higher temperatures, when smoldering overlaps with or follows flaming conditions. In Holocene lake sediments, MAs provide complementary fire proxies to sedimentary charcoal (Elias et al, 2001;Schüpbach et al, 2015;Battistel et al, 2017;Schreuder et al, 2019;Dietze et al, 2019).…”
Section: Background Considerationmentioning
confidence: 99%
“…To reconstruct long-term fire regime shifts, sedimentary charcoal can be used as a classical proxy of fire of various combustion efficiencies (Whitlock and Larsen, 2001;Conedera et al, 2009). Yet, fire intensity reconstructions and 110 the differentiation between surface and crown fires is difficult to specify, especially on long timescales, as well as when considering other fire proxies such as fire scars and fungal spores (Stivrins et al, 2019). Molecular burning proxies are currently being explored to infer source-and temperature-specific fire histories (Kehrwald et al, 2016;Kappenberg et al, 2019;Dietze et al, in review).…”
Section: Fig1mentioning
confidence: 99%
“…Dendroecology, however, can provide insights of unique temporal resolution, because tree rings may allow fire histories to be reconstructed (McBride 1983, Stivrins et al 2019. A recent example of the successful utilization of tree rings in wildfire dendroecology is the precise dating of moss buried stems to quantify postwildfire dynamics of the ASL thickness and ground vegetation recovery in northern Siberia (Knorre et al 2019).…”
Section: Introductionmentioning
confidence: 99%